The Desire of Parenthood: Intuitive Co-parental Behaviors and Quality of Couple Relationship among Italian and Belgian Same-Sex and Opposite-Sex Couples - Miscioscia, Marina; Blavier, Adelaide; Pagone, Paolo R.; Simonelli, Alessandra (Frontiers in Psychology, 2017)
Studies that focused on family issues have allowed a great understanding of the aspects related to its subsystems, such as parenting desire and its expectations, couples’ satisfaction and quality of child’s outcomes. All these aspects are greatly interconnected and contribute to the creation of specific family dynamics, such as the quality of family interactions. The present study focuses on intuitive co-parental behaviors and the quality of couple relationship observed during the decision process (intention and desire) to be (or become) parents. Our first goal was to explore these aspects in a cross-national sample made of Italian and Belgian heterosexual, lesbian and gay couples. We then aimed to evaluate if the degree of internalized homophobia affects co-parental alliance. The quality of couple relationship and co-parental behaviors have been evaluated through the recruitment of a group of 115 stable heterosexual, gay and lesbian couples (230 individuals, 20-50 years of age) without children, who wanted to become parents. We used the Prenatal Lausanne Trilogue Play to evaluate the Co-parental Alliance; the couple’s satisfaction was assessed with the Dyadic Adjustment Scale and the Internalized Homophobia with the MISS-LG. In line with the existent literature, the analysis did not find any difference between lesbian, gay and heterosexual couples in terms of co-parental alliance. High levels of couple adjustment lead to better parental performances among both Italian and Belgian couples. The results suggest also that sexual stigma differs from one country to another, and it has an impact on the capability of managing co-parenting. Clinical implications should be verified in further longitudinal studies in order to observe the impact on the inter-generational transmission of psychopathology.